Broad autism spectrum and obsessive–compulsive symptoms in adults with the fragile X premutation. Issue 6 (17th August 2016) - Schneider, A.; Johnston, C.; Tassone, F.; Sansone, S.; Hagerman, R. J.; Ferrer, E.; Rivera, S. M.; Hessl, D.
Abstract: Objective: Clinical observations and a limited number of research studies provide evidence that the fragile X premutation may confer risk for autism, executive dysfunction, and psychopathology. The link to autism spectrum symptoms and social cognition deficits with the premutation remains uncertain, and thus was the focus of the present investigation. Method: Our sample included 131 individuals, 42 men/22 women with the FMR1 premutation (mean age = 31.83 ± 8.59 years) with a normal neurological exam, and 48 men/19 women healthy age-matched controls (mean age = 29.48 ± 7.29 years). Individuals completed a comprehensive neuropsychological battery with additional assessments for social cognition, broad autism spectrum, and obsessive–compulsive (OC) symptoms. Results: Premutation carriers self-reported higher rates of autism-related symptoms (Autism Quotient; p  = .001). Among males only, premutation carriers showed more atypical social interaction ( p  < .001) and stereotyped behavior ( p  = .014) during standardized clinical examination on the Autism Diagnostic Observation Schedule (ADOS) relative to controls. Female premutation carriers reported significantly higher rates of OC symptoms compared to control females ( p  = .012). Molecular measures defining the expanded premutation ( FMR1 CGG repeat length and/or mRNA) were significantly associated with a measure of theory of mind (Reading the Mind in the Eyes Task). Conclusions: The results of this study indicate a higher rate of broad autism spectrum symptoms in some males with the premutation and provide evidence for an obsessive–compulsive subtype in female premutation carriers.